1972
DOI: 10.1029/jc077i015p02654
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state vertical turbulent diffusion of radon

Abstract: In their interesting paper Cohen et al. [1972] analyze results of a large quantity of painstaking observations and make a determined effort to explain their observations physically in terms of vertical mixing in the atmospheric boundary layer. Much of their discussion is based on conclusions drawn from visual inspection of scatter diagrams, their Figures 6, 7, and 8. In particular, they say. with regard to Figure 6, 'groups i and 2 . . . are not clearly distinguishable by [AT],' and that 'groups 1 and 2 are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…On both high and medium gradient nights, after sunrise Ri B drops sharply to negative values (indicating unstable conditions) and K B rises. Cohen et al (1972) also found a strong relationship between the 6 and 270 m radon gradient and a stability parameter based on the Richardson Number. Figures 10c and d present turbulence statistics from the threedimensional sonic anemometer data at 50 m, computed in hourly bins and composited to match the results from the bulk quantities.…”
Section: Nocturnal Mixing Patternsmentioning
confidence: 72%
See 1 more Smart Citation
“…On both high and medium gradient nights, after sunrise Ri B drops sharply to negative values (indicating unstable conditions) and K B rises. Cohen et al (1972) also found a strong relationship between the 6 and 270 m radon gradient and a stability parameter based on the Richardson Number. Figures 10c and d present turbulence statistics from the threedimensional sonic anemometer data at 50 m, computed in hourly bins and composited to match the results from the bulk quantities.…”
Section: Nocturnal Mixing Patternsmentioning
confidence: 72%
“…On both high and medium gradient nights, after sunrise Ri B drops sharply to negative values (indicating unstable conditions) and K B rises. Cohen et al (1972) also found a strong relationship between the 6 and 270 m radon gradient and a stability parameter based on the Richardson Number.…”
mentioning
confidence: 72%
“…Towers were used to make profile measurements (Moses et al, 1960;Cohen et al, 1972;Ussler et al, 1994;Butterweck et al, 1994), some observations were made at elevated (mountain) sites (Wilkening and Rust, 1972), and later, sampling was conducted using airborne platforms (Kritz et al, 1990. The techniques used for measurements were typically fairly simple.…”
Section: Historical Background: Radon Monitoring and Applicationmentioning
confidence: 99%
“…Although the close relationship of their concentration to atmospheric stability has long been recognized [e.g., Beck and Go•tolak, 1979;Cohen et al, 1972;Fontan et al, 1966;Fujinami and Esaka, 1987; Go•tolak and Beck, 1980;Hosler, 1968;Ikebe et al, 1983; Isra•'l et al., 1966;Ran•qarajan et al, 1974;Servant, 1966], and there have been many reports describing qualitatively the roles of solar radiation and heat emission [e.g., Eisenbud, 1973;Gesell, 1983;Moses et al, 1960;Reiter and Munzert, 1982;Wilkenin•t, 1981], very few have been published which treat their roles quantitatively [Garzon et al, 1986;Quindos et al, 1983]. Radon 222 and its daughter concentrations in surface air should therefore be influenced by solar radiation in the daytime and by heat emission in the nighttime.…”
Section: Introductionmentioning
confidence: 99%